INFLUENCE OF OXIDATIVE STRESS ON THE FUNCTION OF ENDOTHELIUM AND APOPTOSIS IN ARTERIAL HYPERTENSION, POSSIBILITY OF THERAPY WITH AT1-BLOCKER CANDESARTAN - Kravchun, P.G.; Babadzhan, V.D.; Manik, Ibrahim Moosa; Gorbach, T.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
45 patients with moderate hypertension were investigated and candesartan in the dose of 16 mg/d was prescribed during 3 weeks. It was determined, that sings of endothelial dysfunction in patients with arterial hypertension weren’t only enhance formation of endothelin-1 but also included of NO in the processes of albumens freely-radical oxidization. As a result of therapy with candesartan there were braking of surplus albumens peroxide oxidization, activation of antioxidant defense, normalization of nitric oxide synthase, S-nitrosothyol activity and decrease activity of endothelin-1 in blood. Therapy with candesartan leaded to braking apoptosis, diminishing concentration of FAS-ligand in blood.